Sport sponsorship in Finland: the case study of FC JJK Jyväskylä - Szerovay , Mihály (Applied Studies in Agribusiness and Commerce, 2013)
This paper seeks to analyse sport sponsorship in Finland via using the case study of Football Club JJK Jyväskylä from the Finnish Premier League. The results of a master’s thesis conducted on FC JJK fans’ sponsor awareness and sponsor orientation is presented. This research has provided implications to the management of the club, such as how to increase sponsorship efficiency, how to benefit from applying sponsorship alignment as well as relationship marketing. In order to successfully implement the study, an online survey, interviews, and participant observation was utilised. In addition, statistical data were obtained from the club. It has been concluded that JJK fans’ sponsor awareness and attitude stood at a low level, therefore JJK’s sponsorship strategy was advised to be reorganised. Conclusions from this paper might be beneficial for clubs from peripheral football countries, including those from Hungary as well. The size and level of Finnish and Hungarian football clubs are fairly similar and both countries can be considered as peripheral football countries at present.